Achievements and gaps in tef productivity improvement practices in the marginal areas of Northern Ethiopia: implications for future research directions. Issue 1 (2nd January 2017) - Abraha, Mizan Tesfay; Shimelis, Hussein; Laing, Mark; Assefa, Kebebew
ABSTRACT: Tef is the most important crop in Ethiopia and is well-adapted to growing environments, but grain yields are low. The government is therefore promoting the adoption of improved varieties, inorganic fertilizers and new planting techniques. This study gathered information on the use of new agronomic practices and barriers to their adoption through a semi-structured questionnaire administered to 60 farmers or respondents from each of 4 districts of Tigray region in northern Ethiopia viz Laelay-Maichew, Medebay-Zana, Ahferom and Alamata. Data were coded and analysed using SPSS software. Except for animal feed and crop rotation, there were significant differences between districts in the relative importance of several criteria for different uses. Improved varieties were used by the majority of respondents in all districts and fertilizers in all except Alamata where severe moisture stress dictated the choice of variety and reduced fertilizer application. Weed control was mainly by hand except in Alamata where chemical control was common because of the predominance of broad-leaved weeds. Transplanting maximized the yield of tef, but a cost–benefit analysis showed that row sowing was more profitable. The study concluded that new varieties better adapted to the likelihood of reduced rainfall and that respond efficiently to fertilizer inputs need to be developed. Until suitable technologies are available, high labour costs would in part dictate some agronomic practices, even if this led to lower yields.